Addressing Dermatologic Health Disparities: Characterization of a Free Dermatology Clinic for an Uninsured Population - O’Connell, Katie; Bartholomew, Erin; Villanueva, Andrew (Journal of Student-Run Clinics, 2021)
Background: Barriers to accessing dermatologic care are important to address for individuals without health insurance. This report aims to highlight dermatologic health disparities facing the uninsured population, to demonstrate the invaluable impact a monthly student-run free clinic can have on this population, and to encourage the implementation of dermatologic free clinics at other institutions. Methods: Data was collected using the electronic medical record â€œChart Reportsâ€ tool to create a query for total dermatology visits from 2012-2019. Records were reviewed and descriptive data was collected on diagnoses, medications, procedures, and follow-up rates of a student-run dermatology free clinic from 2012-2019. Results: Over this period, dermatologic care was provided to 215 patients and a total of 321 diagnoses were made. The most common diagnoses included atopic dermatitis (26), seborrheic keratosis (21), and acne (17). Twenty-three skin cancer diagnoses were made, including 13 basal cell carcinomas, 8 squamous cell carcinomas, one case of melanoma, and one case of nonmelanoma skin cancer, unspecified. Conclusion: A higher prevalence of atopic dermatitis, melanoma, and non-melanoma skin cancer has been reported in ethnic minorities and people of low socioeconomic status. This aligns with our results and these findings highlight the significant need for improved access to dermatologic screening and follow-up for individuals without health insurance. This report also shows the unique opportunity free clinics have to address dermatologic health disparities in the local community.